Insertion of Host-Derived Costimulatory Molecules CD80 (B7.1) and CD86 (B7.2) into Human Immunodeficiency Virus Type 1 Affects the Virus Life Cycle - Giguère, Jean-François (American Society for Microbiology, 2004)
Human immunodeficiency virus type 1 (HIV-1) carries virus-encoded and host-derived proteins. Recent advances in the functional characterization of host molecules inserted into mature virus particles have revealed that HIV-1 biology is influenced by the acquisition of host cell membrane components. The CD28/B7 receptor/ligand system is considered one of the fundamental elements of the normal immune response. Two major cell types that harbor HIV-1 in vivo, i.e., monocytes/macrophages and CD4(+) T cells, express the costimulatory molecules CD80 (B7.1) and CD86 (B7.2). We investigated whether CD80 and CD86 are efficiently acquired by HIV-1, and if so, whether these host-encoded molecules can contribute to the virus life cycle. Here we provide the first evidence that the insertion of CD80 and CD86 into HIV-1 increases virus infectivity by facilitating the attachment and entry process due to interactions with their two natural ligands, CD28 and CTLA-4. Moreover, we demonstrate that NF-κB is induced by CD80- and CD86-bearing virions when they are combined with the engagement of the T-cell receptor/CD3 complex, an event that is inhibited upon surface expression of CTLA-4. Finally, both CD80 and CD86 were found to be efficiently incorporated into R5- and X4-tropic field strains of HIV-1 expanded in cytokine-treated macrophages. Thus, besides direct interactions between the virus envelope glycoproteins and cell surface constituents, such as CD4 and some specific chemokine coreceptors, HIV-1 may attach to target cells via interactions between cell-derived molecules incorporated into virions and their natural ligands. These findings support the theory that HIV-1-associated host proteins alter virus-host dynamics.